Hybrid tomato seed production under protected conditions - Singh, Yogendra; Pandey, Sushil; Lal, Sandeep Kumar; Singh, Praveen K; Pandey, Chitra Devi; Hussain, Zakir; Yadav, D K (Indian Horticulture, 2019)
Hybrid tomato seed production is primarily taken up in the Ranebennur area of Karnataka. With more than hundred private companies taking up seed production, competition for skilled labourers has grown tremendously, resulting in high labour cost. Moreover, with same crops grown since 25 years, there is high pest and disease infestation. Hybrid tomato seeds cost is quite high, and can be a remunerative business for small industries and rural entrepreneurs of North India who cannot afford to take up seed production in Ranebennur. However, due to extreme cold and frost during December-January in northern India, seed production technology needs to be standardized.